Multi-omics reveals the mechanism of Trimethylamine N-oxide derived from gut microbiota inducing liver fatty of dairy cows - Chenlei Li; Feifei Wang; Yongxia Mao; Yanfen Ma; Yansheng Guo (BMC Genomics)
Abstract Background Trimethylamine N-oxide (TMAO) is a metabolite produced by gut microbiota, and its potential impact on lipid metabolism in mammals has garnered widespread attention in the scientific community. Bovine fatty liver disease, a metabolic disorder that severely affects the health and productivity of dairy cows, poses a significant economic burden on the global dairy industry. However, the specific role and pathogenesis of TMAO in bovine fatty liver disease remain unclear, limiting our understanding and treatment of the condition. This study aims to construct a bovine fatty liver cell model using an integrated approach that combines transcriptomic, proteomic, and metabolomic data. The objective is to investigate the impact of TMAO on lipid metabolism at the molecular level and explore its potential regulatory mechanisms. Results We established an in vitro bovine fatty liver cell model and conducted a comprehensive analysis of cells treated with TMAO using high-throughput omics sequencing technologies. Bioinformatics methods were employed to delve into the regulatory effects on lipid metabolism, and several key genes were validated through RT-qPCR. Treatment with TMAO significantly affected 4790 genes, 397 proteins, and 137 metabolites. KEGG enrichment analysis revealed that the significantly altered molecules were primarily involved in pathways related to the pathology of fatty liver disease, such as metabolic pathways, insulin resistance, hepatitis B, and the AMPK signaling pathway. Moreover, through joint analysis, we further uncovered that the interaction between TMAO-mediated AMPK signaling and oxidative phosphorylation pathways might be a key mechanism promoting lipid accumulation in the liver. Conclusions Our study provides new insights into the role of TMAO in the pathogenesis of bovine fatty liver disease and offers a scientific basis for developing more effective treatment strategies.